3D FSS with multiple transmission zeros and pseudo elliptic response - Bimal Raj Dutta; Binod Kumar Kanaujia; Chhaya Dalela (Bulletin of Electrical Engineering and Informatics, 2019)
The three-dimensional frequency selective surface (3D FSS) with band reject multiple transmission zeros and pseudo-elliptic response is designed from two-dimensional (2D) periodic array of shielded micro strip lines to realize wide out-of–band radio wave rejection. The 3D FSS array consists of multimode cavities whose coupling with air can be controlled to obtain a desired frequency range. The proposed FSS with shorting via to ground exhibits pseudo-elliptic band-reject response in the frequency range from 6GHz to 14GHz. As the plane wave of linear polarization incidents perpendicularly to the shielded micro strip line with perfect electric conductor (PEC) and perfect magnetic conductor (PMC) boundary walls, two quasi-TEM modes are obtained known as air mode and substrate mode. The first 3D FSS design is a combination of two or more resonators. Furthermore, second 3D FSS design with three shorting vias result more elliptic band reject frequency response and a pass band transmission pole. All in phase resonators of design give transmission poles and out of phase combination of resonators give transmission zeros respectively. The proposed 3D FSS is designed and simulated using Ansys HFSS software. These designs exhibit an improved performance for many practical applications such as antenna sub-reflector, and spatial filters.